Exploring the Socio-cultural Identity of Secondary Level English Teachers in Nepal: A Narrative Perspective - Karki, Sujeet (Journal of Janta Multiple Campus, 2025)
Teacher identity has become a crucial part and an important aspect of teacher professional development. It has become a significant aspect of research in the present day. This research aims to explore the perspective of how socio-cultural factors and their related identity are constructed within the classroom environment. It mainly focuses on the beliefs, attitudes, and social status that English teachers hold and practice. The teachers for this study were chosen using a purposive sampling procedure. By adopting a qualitative research design, the data was collected from four EFL teachers of the Lalitpur district using semi-structured interviews. The research indicates that EFL teachers assimilate themselves in sociocultural settings to construct their identity. They try to adjust to the specific context and working environment through interaction with others. Moreover, teachers have a vital role in social status, recognition, context, beliefs, and practices, which contribute to their position in society.